CryptMAIL: Keamanan Ganda Email Menggunakan Algoritma Kriptografi - Virra Retnowati A’izzah; Dwi Ramti Asih; Anggi Putri Meriani; Alam Rahmatulloh (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The development of technology and information has changed the way humans communicate. Email is an online correspondence service that makes it easier for users to exchange information and communicate with other parties. The convenience offered attracts many people to switch to using email as a medium for exchanging information, and this creates new opportunities for cybercriminals to take action. Problems with email such as data or information leaks, file misuse or message theft due to negligence or others can occur. One way to anticipate this is to implement Cryptographic Techniques. Cryptography is an encryption technique to hide confidential messages from plaintext messages into ciphertext messages that are difficult to understand. In this study, we will discuss the implementation of cryptography with the AES-128 and RC4 algorithms for encryption and decryption of messages and file attachments sent via email. The result of this research is a web-based application 'CryptMAIL' which can encrypt and decrypt messages using the AES-128 and RC4 cryptographic algorithms. The 'CryptMAIL' application is expected to provide double security to anticipate security problems in email.